2009
DOI: 10.1038/jcbfm.2009.182
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Levels of Growth Factors Are Associated with Good Outcome in Intracerebral Hemorrhage

Abstract: In experimental models, growth factors (GFs) such as vascular endothelial growth factor (VEGF), Angiopoietin 1 (Ang-1), or granulocyte-colony stimulating factor (G-CSF) mediate brain recovery after intracerebral hemorrhage (ICH). Our aim was to study the association between serum levels of GF and clinical outcome in patients with ICH. A total of 95 patients with primary ICH (male, 66.3%; mean age, 67.8 ± 9.8 years) were prospectively included in the study within 12 h from symptoms onset. The main outcome varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 25 publications
4
37
2
5
Order By: Relevance
“…[18][19][20] In a clinical ICH study, high levels of VEGF and Ang-1 at 72 hours after symptom onset were associated with good functional outcome and reduced lesion volume. 11 In our study, neither VEGF nor Ang-1 were associated with PHE or clinical outcome. This could be a result of the different time points of GFs assessment.…”
Section: March 2013mentioning
confidence: 81%
See 1 more Smart Citation
“…[18][19][20] In a clinical ICH study, high levels of VEGF and Ang-1 at 72 hours after symptom onset were associated with good functional outcome and reduced lesion volume. 11 In our study, neither VEGF nor Ang-1 were associated with PHE or clinical outcome. This could be a result of the different time points of GFs assessment.…”
Section: March 2013mentioning
confidence: 81%
“…3 The impact of PHE on clinical outcome is still under debate. [4][5][6][7] Matrix metalloproteinase (MMP)-3 and MMP-9, [8][9][10] as well as growth factors (GFs) such as vascular endothelial growth factor (VEGF) and Angiopoietin-1 (Ang-1), 11 are expressed in abnormally high concentrations in brain and peripheral blood in ICH patients. In ICH animal models, elevated MMP-9 and MMP-3 contribute to blood-brain barrier (BBB) disruption, 12,13 brain edema, 14,15 and neuronal cell death.…”
mentioning
confidence: 99%
“…A prospective study on primary ICH patients has demonstrated that high serum levels of growth factors such as vascular endothelial growth factor, glanulocytecolony stimulating factor (G-CSF), and angiopoietin 1 are associated with good functional outcome and reduced lesion volume (62). With regard to G-CSF, daily intraperitoneal injection of this cytokine from 2 h after induction of ICH by collagenase in rats resulted in improved recovery from neurological deficits.…”
Section: Growth Factors and Cytokinesmentioning
confidence: 99%
“…G-CSF was the only cytokine of 23 measured whose serum levels were elevated after traumatic brain injury in a murine model (Dohi et al, 2014). High levels of G-CSF are associated with better functional outcome and reduced lesion volume in intracranial hemorrhage (Sobrino et al, 2009). G-CSF is elevated 2 h after controlled cortical injury, but not at later time points in mice, which may make it useful in determining the timing of injury (Dohi et al, 2014).…”
Section: Granulocyte Colony Stimulating Factor (G-csf)mentioning
confidence: 98%